Analysis of Informatics Topics in Accreditation Council for Graduate Medical Education Program Requirements - Rohan, Thomas Z.; Nayak, Ruhi; Yang, Kevin; Nambudiri, Vinod E.; Kim, Ellen (Applied Clinical Informatics, 2024)
Background There is growing recognition of the need to incorporate informatics education in U.S. residencies. Medical residency training programs are critical in shaping system change and can play a pivotal role by incorporating clinical informatics (CI) based learning into their training requirements.Objectives We searched the Accreditation Council for Graduate Medical Education (ACGME) Residency Program Requirements effective July 1, 2023, to assess the inclusion of CI topics for all medical residency specialties to assess the relative levels of CI knowledge expected by graduates.Methods We performed independent full-text search queries of 23 informatics-related keywords (e.g., electronic health record, innovation, database) in the ACGME Residency Program Requirements of 24 medical specialties.Results All specialties' requirements contained at least five different keywords, with the total count ranging from 25 to 42 (mean: 32.00; standard deviation: 5.09). Pathology contained the highest counts with 42, followed by internal medicine and family medicine with 41 each. Pathology included the most distinct keywords (11). The most common keywords were “leadership” (62%) and “electronic health record” (10%). There were no specific mentions of several keywords—including “analytics,” “artificial intelligence,” and “machine learning”—within any program requirements. Although the ACGME Residency Program Requirements state that residents must demonstrate competence in using information technology to optimize learning, the extent is not fully specified; only 10 programs mention the keyword “information technology” within their specialty guidelines.Conclusion The integration of CI education varies across specialties and may be even more variable across programs. Our study highlights potential opportunities for further standardization and integration of CI into resident curriculum requirements in order to better prepare future physician workforces for a changing medical landscape. We encourage educators, residency review committees, and national specialty organizations to consider further exploring the incorporation of CI content into residency training program requirements.
Keywords: education; Accreditation Council for Graduate Medical Education; professional training; clinical informatics; workforce